Kotumsaridae, a new family of subterranean amphipod crustaceans from India, with description of Kotumsaria bastarensis, new genus, new species. Zootaxa, 1589, 33–46. (ERRATUM) - Messouli, M.; Holsinger, J. R.; Reddy, Y. R. (Zootaxa, 2007)
ERRATUM